Konsep Taubat Menurut Islam dan Kristian dari Perspektif Perbandingan: The Concept of Repentance in Islam and Christianity from Comparative Perspectives - Haji Dollah, Sri Rahayu; Mohd Khambali @ Hambali, Khadijah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2016)
The value of repentance is emphasized in both religions of Islam and Christianity and it is regarded as the method of purification of the soul. Both religions consider the repentance as a liaison between God and man and it is a way to achieve salvation. Apparently, the concept of repentance in the aspect of remorse and forgiveness of sins reflected in much of the religion of Islam is found similar to the concept of repentance found in the religion of Christianity. However, there are apparent differences in term of the goals and the implementation aspects of repentance. Islam sets the aspects of justice in repentance in line with the human nature and the divine concept. While, Christianity puts the repentance as the key to faith in God without being able to assure justice to human beings and their rights. Therefore, the present paper examines the concept of repentance from the Islamic viewpoint and the Christianity perspective. The contextual comparison method was used in this study. The findings show the significant differences of the application of repentance and justice between Islam and Christianity and there are practical disparities in Christianity.